2008
DOI: 10.1152/ajpheart.00650.2007
|View full text |Cite
|
Sign up to set email alerts
|

Increased shear stress with upregulation of VEGF-A and its receptors and MMP-2, MMP-9, and TIMP-1 in venous stenosis of hemodialysis grafts

Abstract: Venous injury and subsequent venous stenosis formation are responsible for hemodialysis graft failure. Our hypothesis is that these pathological changes are in part related to changes in wall shear stress (WSS) that results in the activation of matrix regulatory proteins causing subsequent venous stenosis formation. In the present study, we examined the serial changes in WSS, blood flow, and luminal vessel area that occur subsequent to the placement of a hemodialysis graft in a porcine model of chronic renal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 60 publications
6
94
2
Order By: Relevance
“…However, little is known about the relationship between hemodynamic force and MMP-2 secretion by ECs, although MMP expression under high shear stress increases in grafted whole vessels, including smooth muscle and inflammatory cells (Abbruzzese et al 1998;Korshunov and Berk 2003;Misra et al 2008). Our current study using gelatinase activity assay estimated by zymography and measurement of MMP-2/GFP fusion protein showed that MMP-2 protein was remarkably lower in a conditioned medium of ECs under high shear stress than under static control.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the relationship between hemodynamic force and MMP-2 secretion by ECs, although MMP expression under high shear stress increases in grafted whole vessels, including smooth muscle and inflammatory cells (Abbruzzese et al 1998;Korshunov and Berk 2003;Misra et al 2008). Our current study using gelatinase activity assay estimated by zymography and measurement of MMP-2/GFP fusion protein showed that MMP-2 protein was remarkably lower in a conditioned medium of ECs under high shear stress than under static control.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies of AVGs have demonstrated a differential upregulation of MMP-2 at the graft-vein anastomosis, with early expression (9 days) in the adventitia and a later expression (19 days) within the intima, supporting the concept of cellular migration from the adventitia to the intima 86 . Furthermore, linkages between hemodynamic shear stress and the expression of oxidative stress markers and cytokines have also been described in a porcine model of AVG stenosis 87 . Clinical studies of stenotic and thrombotic AVGs and AVFs have also demonstrated an upregulation of MMPs 88 , and have documented the co-localization of oxidative stress markers with inflammatory cytokines such as transforming growth factor-beta (TGF-), and platelet-derived growth factor (PDGF), within the neointima of both stenotic AVGs and AVFs 60 .…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Hemodynamic sheer stresses play a significant role in development of neointimal hyperplasia 87,112,206,207 . Therefore, altering the sheer stress pattern to prevent turbulent, lowflow, and low-sheer stresses could reduce the development of neointimal hyperplasia.…”
Section: Improving Hemodynamicsmentioning
confidence: 99%
“…More specifically, fluid shear stress is thought to trigger biochemical cascades within the endothelial cells of the developing heart that regulate chamber and valve morphogenesis [2,9,10]. Fluid shear is also known to increase transcription rates of several genes that are thought to also be involved in the regulation of cardiac morphogenesis, such as vascular endothelial growth factor [11,12] and endothelial transforming growth factor [13]. One study has found that fluid shear might also increase the conduction velocities of action potentials in the myocardial layer of the developing heart [14].…”
Section: Introductionmentioning
confidence: 99%